2019
DOI: 10.31649/1997-9266-2019-143-2-91-98
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Thermal Control Data Spindle Supports Desktop Screw-Cutting Lathe

Abstract: Ключевые слова: тепловой контроль, токарно-винторезный станок, шпиндельный узел, подшипники качения, энергоэффективные технологии, определяющий параметр, скорость нагрева.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Machines and aggregates are subjected to periodic diagnostic examination and testing to determine the technical state of mechanical nodes by methods of nondestructive control. There is a large number of control techniques, but the main condition is to provide reliable test results with minimal energy consumption, which is achieved by the correct choice of control method [445]. The automation of the control process is a major way to eliminating people floating on the results of measurements, as well as ensuring the efficiency of data processing and obtaining results, which increases the energy efficiency of diagnostic methods.…”
Section: Automation Of Processing Results Of Diagnostic Surveys and Testing Of Bearing Knotsmentioning
confidence: 99%
“…Machines and aggregates are subjected to periodic diagnostic examination and testing to determine the technical state of mechanical nodes by methods of nondestructive control. There is a large number of control techniques, but the main condition is to provide reliable test results with minimal energy consumption, which is achieved by the correct choice of control method [445]. The automation of the control process is a major way to eliminating people floating on the results of measurements, as well as ensuring the efficiency of data processing and obtaining results, which increases the energy efficiency of diagnostic methods.…”
Section: Automation Of Processing Results Of Diagnostic Surveys and Testing Of Bearing Knotsmentioning
confidence: 99%
“…A study was carried out on the pattern of changes in the heating temperature of the rolling bearings in a screw-cutting lathe [25] and a vertical drilling machine during tests without load. It was confirmed that under a regular heating mode, the heating rate of the rolling bearings in a spindle assembly in an efficient technical condition does not exceed 1.1 °C/min.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%